Restructuring emergency eye services during COVID-19 in a tertiary referral centre. (2nd December 2020) - Moussa, George; Mushtaq, Fizza; Mandal, Priyanka; Mathews, Namita; Royal, Ben; Manjunatha, Nonavinakere; Lee, Rynn
Abstract : Background/aims: Maintaining emergency eye services is crucial during the COVID-19 pandemic. This article describes the introduction of a new restructured referral pathway to reduce the burden on healthcare providers and create a safe environment. Methods: During January and February 2020 (group 1), all appointments were face-to-face with a walk-in eye casualty. The first audit cycle comprised all patients in group 1. The primary audit criteria were discharge rates, referral to subspeciality and reattendance. In April 2020, a remodelled system was implemented in which walk-in attendance ceased and was replaced with telephone triage coupled with digital imaging via NHS email for remote clinical review. Patients requiring further assessment following this triage were invited in for face-to-face appointments. A reaudit was conducted during April–July 2020 (group 2) following implementation of these COVID-19 protocol changes. Results: In group 1, 2868 appointments (100.0%) were face-to-face and in group 2 4870 (100.0%) appointments were telephone consults that resulted in 2639 (54.2%) face-to-face appointments. The rate of discharge in the first cycle and second cycle were 55.3% and 76.9% respectively ( P <0.0001). Furthermore 2298 (47.2%) patients were able to be discharged following telephone consultation in group 2. Conclusions: Using this telephone and digital imaging review triage system, the authors have demonstrated a significant reduction in the need for face-to-face reviews. The reduction in avoidable patient face-to-face reviews allows the system to move from saturated to sustainable while increasing accessibility to services for patients who may not be able to present for face-to-face review. This complete audit cycle successfully charts interventions that maximise accessibility, reduce unnecessary hospital visits and deliver safe and prompt management during the pandemic.